Low interfacial pH discloses the favorable biodegradability of several Mg alloys. (1st April 2022) - Wang, Cheng; Song, Ci; Mei, Di; Wang, Linqian; Wang, Wenhui; Wu, Ting; Snihirova, Darya; Zheludkevich, Mikhail L.; Lamaka, Sviatlana V.
Abstract: Low interfacial pH (7.5–8.0) and corrosion rate were found for several Mg alloys (CP-Mg, UHP-Mg, Mg-0.15 wt%Ca, Mg-4 wt%Ag) in Ca 2+ -containing Hanks' Balanced Salt Solution (HBSS, pH initial bulk = 7.4) at 37 °C under hydrodynamic condition. Low interfacial pH and corrosion rate originated from the facilitated formation of the protective calcium-phosphate-rich precipitates at 37 °C. This study indicates that Mg degradation in a quasi-physiological environment causes only slight alkalization (pH < 8.0), as opposed to the high local and bulk pH (ca. 10.4) characteristic for Mg in NaCl electrolyte. It is also stressed that no synthetic pH buffers should be added to constantly supplied Ca 2+ -containing HBSS. Highlights: Low interfacial pH (7.5–8.0) was found for several Mg alloys in flowing 37 °C HBSS. Lower corrosion rates were measured for several Mg alloys in HBSS at 37 °C than RT. Synthetic pH buffers are not recommended for in vitro studies of biodegradable Mg. Local pH was featured in different dimensions: midpoint, linescan, mapping, profile. The comparison with cross-section image of in vivo Mg implant supports the findings.